Computer safety, reliability, and security : SAFECOMP 2015 Workshops, ASSURE, DECSoS, ISSE, ReSA4CI, and SASSUR, Delft, the Netherlands, September 22, 2015, Proceedings /: SAFECOMP 2015 Workshops, ASSURE, DECSoS, ISSE, ReSA4CI, and SASSUR, Delft, the Netherlands, September 22, 2015, Proceedings. (2015) - Unknown
No abstract available